2016
DOI: 10.1080/10715762.2016.1244821
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase deficiency enhances zymosan phagocytosis associated with up-regulation of surface expression of CD11b in mouse neutrophils

Abstract: Myeloperoxidase (MPO), a major component of neutrophils, catalyzes the production of hypochlorous acid (HOCl) from hydrogen peroxide and chloride anion. Phagocytosis is a critical event induced by neutrophils for host defense and inflammation. Interestingly, we found that MPO-deficient (MPO) neutrophils engulfed larger amounts of zymosan than wild-type neutrophils. Blocking of the CD11b subunit of complement receptor 3 (CR3) as well as inhibition of focal adhesion kinase (FAK) and extracellular signal-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Free MPO by binding to CD11b/CD18 has also been shown to induce neutrophil activation in an autocrine fashion promoting MAPK and NFkB signaling, ROS production and degranulation (12). Furthermore, MPO KO PMNs were suggested to better phagocyte zymosan particles due to slightly elevated levels of CD11b and the resulting induction of FAK/ ERK signaling (13). However, by doing careful examination of CD11b expression, which included BM-PMNs, circulating blood PMNs with and without stimulation, as well as following adoptive competitive transfer of WT and MPO KO PMNs into inflamed recipient circulation we found no significant differences in CD11b expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free MPO by binding to CD11b/CD18 has also been shown to induce neutrophil activation in an autocrine fashion promoting MAPK and NFkB signaling, ROS production and degranulation (12). Furthermore, MPO KO PMNs were suggested to better phagocyte zymosan particles due to slightly elevated levels of CD11b and the resulting induction of FAK/ ERK signaling (13). However, by doing careful examination of CD11b expression, which included BM-PMNs, circulating blood PMNs with and without stimulation, as well as following adoptive competitive transfer of WT and MPO KO PMNs into inflamed recipient circulation we found no significant differences in CD11b expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, MPO paracrine modulation of PMN activity particularly stands out. Free MPO has been shown to bind CD11b at the PMN surface and via these interactions, trigger MAPK-and NFkB-dependent ROS production and degranulation by PMNs (12) or improve phagocytosis via the induction of FAK/ERK signaling (13). MPO has also been shown to provide adhesive support for PMNs (14) and modulate both Ca 2+ levels and cytoskeleton organization (15), suggesting its potential role in PMN trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…MPO deficiency also reportedly had enhanced phagocytic capability through the absence of ERK1/2 signalling [ 62 ]. Lung neutrophil influx induced by LPS in mice was attenuated in MPO knockout mice [ 63 ].…”
Section: Mpo: It's In (Most Of) Our Genesmentioning
confidence: 99%
“…Furthermore, neutrophils treated with stimuli are rich in MPO-DNA complexes ( 38 ) and, in turn, MPO can regulate the function and immune response of neutrophils. Recent research has shown that MPO can affect the degranulation of neutrophils and improve their phagocytosis ( 39 ), and it can also “break” the migration of neutrophils and prevent their accumulation ( 15 ). The relationship between MPO in CRC and preoperative neutrophil counts is yet to be reported.…”
Section: Discussionmentioning
confidence: 99%